ANALISIS PROYEKSI POSTERO ANTERIOR BILATERAL PADA PEMERIKSAAN BONE AGE DENGAN GANGGUAN PERTUMBUHAN DI RSUD SLEMAN - Laura Ariwisnu; Ike Ade Nur Liscyaningsih; Ari Anggraeni (JHN: Journal of Health and Nursing, 2026)
Bone age assessment is a radiographic procedure used to evaluate skeletal maturity in children with growth disorders. While the left posteroanterior (PA) projection is the standard method, the use of bilateral PA projections for specific conditions was observed at the Radiology Department of Sleman Regional General Hospital (RSUD Sleman). This study aimed to examine the bone age assessment techniques and the rationale for selecting either the left PA or bilateral PA projection for patients with growth disorders at the hospital. A qualitative case study approach was employed, focusing on two patients with growth disorders. The study was conducted at the Radiology Department of RSUD Sleman between September 2025 and June 2026. Data were gathered through observation, in-depth interviews with three radiographers, a radiologist, and a pediatrician, as well as through documentation and a literature review. Data analysis involved data reduction, data presentation, and conclusion drawing. The results revealed that bone age assessments utilized the left PA projection as the standard procedure, with bilateral PA projections reserved for specific conditions. The left PA projection was performed with the central point at the third metacarpophalangeal joint and a focal-film distance (FFD) of 100 cm, whereas the bilateral PA projection utilized a central point positioned between the two hands, also with an FFD of 100 cm. The left PA projection was selected because it met diagnostic requirements for bone age assessment and adhered to the ALARA (As Low As Reasonably Achievable) radiation protection principle. Conversely, the bilateral PA projection was selectively used for patients with suspected congenital anomalies, deformities, trauma, or asymmetrical growth to compare the ossification development of both hands.